Atypical cardiopulmonary manifestations in pediatric Behçet's disease. Issue 12 (25th September 2020) - Ben‐David, Yael; Gur, Michal; Ilivitzki, Anat; Khoury, Asaad; Bentur, Lea; Butbul Aviel, Yonatan
Abstract: Background: Behçet's disease (BD) is a multisystem autoinflammatory disease of unknown etiology. Cardiopulmonary involvement is rare, especially in young patients, and carries high morbidity and mortality rates. Aim: Of 26 patients with pediatric BD enlisted in our center, we encountered three patients with severe atypical cardiorespiratory presentations. Our aim was to describe the manifestations and the course that led to the diagnosis of BD. Results: Three adolescents presented with intracardiac thrombi and left anterior descending obstruction causing myocardial infarction, pulmonary artery aneurysm with pulmonary embolism in situ, and suspected epiglottitis. Two patients had a delayed diagnosis of BD, and all had a good response to anti‐inflammatory agents. Conclusions: This study demonstrated that pediatric BD is associated with atypical cardiopulmonary manifestations which maybe life threatening. Since diagnosis maybe challenging, a high index of suspicion is needed especially in young patients, to promptly diagnose and treat these complications. Cardiopulmonary signs and symptoms, though uncommon, maybe the first manifestation and a clue to the diagnosis of this rare disease.